DEFINITION subst1_gen_lift_eq()
TYPE =
∀t:T
.∀u:T
.∀x:T
.∀h:nat
.∀d:nat
.∀i:nat
.le d i
→(lt i (plus d h)
→(subst1 i u (lift h d t) x)→(eq T x (lift h d t)))
BODY =
assume t: T
assume u: T
assume x: T
assume h: nat
assume d: nat
assume i: nat
suppose H: le d i
suppose H0: lt i (plus d h)
suppose H1: subst1 i u (lift h d t) x
we proceed by induction on H1 to prove eq T x (lift h d t)
case subst1_refl : ⇒
the thesis becomes eq T (lift h d t) (lift h d t)
by (refl_equal . .)
eq T (lift h d t) (lift h d t)
case subst1_single : t2:T H2:subst0 i u (lift h d t) t2 ⇒
the thesis becomes eq T t2 (lift h d t)
by (subst0_gen_lift_false . . . . . . H H0 H2 .)
eq T t2 (lift h d t)
we proved eq T x (lift h d t)
we proved
∀t:T
.∀u:T
.∀x:T
.∀h:nat
.∀d:nat
.∀i:nat
.le d i
→(lt i (plus d h)
→(subst1 i u (lift h d t) x)→(eq T x (lift h d t)))